Erratum to: Quantitative physiology and elemental composition of Kluyveromyces lactis CBS 2359 during growth on glucose at different specific growth rates - Dias, Oscar (2018)
In the original publication of the article, the below mentioned errors have appeared. The correct text is provided in this erratum. In the abstract section, the sentence ‘‘This dataset serve’’ should be replaced as ‘‘This dataset serves’’. Also, the reference ‘‘Basso TO, Gomes FS, Lopes ML, et al (2014) Homo- and heterofermentative lactobacilli differently affect sugarcane-based fuel ethanol fermentation.Antonie Van Leeuwenhoek105:169–177. doi:10.1007/s10482-013-0063-6’’ should be replaced as ‘‘Basso TO, Dario MG, Tonso A, Stambuk BU, GombertAK(2010)Insufﬁcienturacilsupplyinfullyaerobic chemostat cultures of Saccharomyces cerevisiae leads torespiro-fermentative metabolism anddouble nutrientlimitation. Biotechnol Lett 32:973–977. doi: 10.1007/ s10529-010-0248-2’’. Finally, in the Table 2 footnote, ‘‘according to (Heijnen 1981)’’ should be replaced as ‘‘according to Heijnen (1981)’’.